Evaluation of the Production of Dissolved Organic Matter by Three Marine Bacterial Strains - Goto, Shuji; Tada, Yuya; Suzuki, Koji; Yamashita, Youhei (Frontiers in Microbiology, 2020)
A large part of marine dissolved organic matter (DOM) is considered to be recalcitrant DOM (RDOM) produced by marine bacteria. However, it is still unclear whether differences in bacterial species and/or physiology control the efficiency of RDOM production. Here, batch culture experiments with glucose as the sole carbon source were carried out using three model marine bacterial strains, namely, Alteromonas macleodii (Alt), Vibrio splendidus (Vib) and Phaeobacter gallaeciensis (Pha). Dissolved organic carbon (DOC) concentrations drastically decreased during the exponential growth phases of these bacteria due to the consumption of glucose. The efficiency of bacterial DOC production at the end of incubation was largely different among the strains and was higher for Vib (20%) than for the other two strains (Alt, 4%; Pha, 6%). All strains produced fluorescent DOM (FDOM), including humic-like FDOM which is considered as recalcitrant component in the ocean, even though the composition of bacterial FDOM was also different among the strains. The efficiency of humic-like FDOM production during the exponential growth phase was different among the bacterial strains; that is, Pha produced humic-like FDOM efficiently compared with the other two species. The efficiency of humic-like FDOM production with mineralization of organic matter was lower during the exponential growth phase than during the stationary phase of Alt and Pha. Four processes for the production of bacterially derived recalcitrant humic-like FDOM are suggested from this study: (1) production during active growing (in all strains), (2) production with the reutilization of bacterial DOM (Alt), (3) production with the consumption of cellular materials (Pha), and (4) release from lysis (Vib). Our results suggest that bacterial species and physiology can regulate RDOM production and accumulation in the ocean.